Ginsenoside Rb1 Attenuates Triptolide-Induced Cytotoxicity in HL-7702 Cells via the Activation of Keap1/Nrf2/ARE Pathway - Peng, Hulinyue; You, Longtai; Yang, Chunjing; Wang, Kaixin; Liu, Manting; Yin, Dongge; Xu, Yuchen; Dong, Xiaoxv; Yin, Xingbin; Ni, Jian (Frontiers in Pharmacology, 2022)
Triptolide (TP) is the major bioactive ingredient extracted from Tripterygium wilfordii Hook F, which exerts anti-inflammatory, antirheumatic, antineoplastic and neuroprotective effects. However, TP-induced severe hepatotoxicity limits its clinical application. Ginsenoside Rb1 was reported to possess potential effect in hepatoprotective, but its mechanism has not been fully investigated. This study was aimed at exploring whether ginsenoside Rb1 possesses protective effect TP-induced on hepatotoxicity in HL-7702 cells and the underlying mechanism. This study declared that ginsenoside Rb1 combined with TP effectively reversed TP-induced cytotoxicity in HL-7702 cells. Apoptosis induced by TP was suppressed by ginsenoside Rb1 via inhibition of death receptor-mediated apoptotic pathway and mitochondrial-dependent apoptotic pathway. The Bax/Bcl-2 ratio and cleaved caspase-8, Fas, cleaved PARP, cleaved caspase-3, and -9 expressions were remarkably inhibited by pretreatment of ginsenoside Rb1. Furthermore, ginsenoside Rb1 reversed the S and G2/M cell cycle arrest induced by TP in HL-7702 cells by upregulating CDK2, cyclin A expression and downregulating the expression of cyclin E, p53, p21 and p-p53. Moreover, ginsenoside Rb1 increased GSH and SOD levels, while decreased the ROS and MDA levels. Ginsenoside Rb1 pretreatment enhanced the expression of nuclear factor-erythroid 2-related factor 2 (Nrf2), total Nrf2, NAD(P)H: quinone oxidoreductases-1 (NQO-1), HO-1, and Keap1/Nrf2 complex. Therefore, ginsenoside Rb1 effectively alleviates TP-induced hepatotoxicity through activating oxidative stress-mediated apoptosis pathway and the Keap1/Nrf2/ARE antioxidant pathway.